2005
DOI: 10.1002/ab.20060
|View full text |Cite
|
Sign up to set email alerts
|

Violent behavior in schizophrenic patients: relationship with clinical symptoms

Abstract: Considerable evidence suggests that violent behavior observed in schizophrenic patients is motivated by psychotic symptomatology. The understanding of violence in schizophrenic patients requires consideration of psychiatric symptomatology. Objective: This study investigated the relationship between violent behavior and psychiatric symptomatology in schizophrenic patients. Method: One hundred and thirteen patients were recruited. Thirteen patients were excluded due to concomitant substance abuse six months prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…(1997b) reported that positive symptoms of schizophrenia were significant independent predictors of violence in regression models measuring the impact of hostility and PANSS scores (OR = 1.15, 95% CI = 1.05, 1.23, P < 0.01), antisocial traits and PANSS scores (OR = 1.24, 95% CI = 1.11, 1.43, P < 0.01), history of aggression during previous admission (OR = 1.14, 95% CI = 1.03, 1.25, P < 0.05), and history of aggression during outpatient treatment (OR = 1.24, 95% CI = 1.09, 1.43, P < 0.01). These findings were substantiated by a more recent study (Fresán et al . 2005), which found that PANSS positive symptoms score was significantly correlated with physical aggression against others ( P = 0.02, r 2 = 0.0484).…”
Section: Resultssupporting
confidence: 76%
“…(1997b) reported that positive symptoms of schizophrenia were significant independent predictors of violence in regression models measuring the impact of hostility and PANSS scores (OR = 1.15, 95% CI = 1.05, 1.23, P < 0.01), antisocial traits and PANSS scores (OR = 1.24, 95% CI = 1.11, 1.43, P < 0.01), history of aggression during previous admission (OR = 1.14, 95% CI = 1.03, 1.25, P < 0.05), and history of aggression during outpatient treatment (OR = 1.24, 95% CI = 1.09, 1.43, P < 0.01). These findings were substantiated by a more recent study (Fresán et al . 2005), which found that PANSS positive symptoms score was significantly correlated with physical aggression against others ( P = 0.02, r 2 = 0.0484).…”
Section: Resultssupporting
confidence: 76%
“…The suggestion that individuals with schizophrenia are more at risk of perpetrating violence than normal controls has led researchers to consider specific symptoms of psychosis. Some studies have suggested that one route to violence in psychosis is suffering acute symptoms (Volavka, 2013), and that more severe psychotic symptoms may be linked to greater violence (Fresán et al, 2005). Recent reviews have suggested that the content of psychotic symptomology may be relevant.…”
Section: Rationalementioning
confidence: 99%
“…Risk for aggression is increased in patients with schizophrenia compared to individuals without serious mental illness (Swanson et al, 1990; Steadman et al, 1998; Brennan et al, 2000). Positive psychotic symptoms may be more severe in violent schizophrenic patients (Krakowski et al, 1999; Fresán et al, 2005), however, frontally mediated functions such as social cognition (Weiss et al, 2006) and impulse control (Hoptman et al, 2002; Kumari et al, 2009) are also impaired and there is evidence for relationships between frontotemporal disconnections and aggression (Hoptman et al, 2002; Hoptman et al, 2010). Aggression is also increased in non-psychotic conditions that affect impulse control.…”
Section: Introductionmentioning
confidence: 99%